The testosterone barrier in sport - Raúl Sánchez García (Universidad Pablo de Olavide, 2022)
World Athletics (formerly known as IAAF) has recently published the eligibility regulations for female classification that apply to running events from 400 meters up to the mile. The regulations have prevented some elite women athletes with DSD (Difference of Sexual Development) to compete or have made some of them to change their preferred running event in the 2020 Tokyo Olympics. According to World Athletics, female hyperandrogenism (a biological anomaly that naturally produces a high level of testosterone) must be in some way "compensated" to respect the fair play of the competition. Nonetheless, such argument rests upon a problematic assumption: hyperandrogenic women are not "natural" women -at least when it comes to compete in sports- so their "not-normal" condition must be fixed to meet the standards. Norbert Elias's process-sociology helps to place the case of hyperandrogenic sportswomen within a broader context of power relations. In this fashion, we see that the case becomes problematic because these women athletes are perceived as a threat/disruption of one of the vertebral categories of sport: sex/gender. The testosterone barrier is to sex/gender what the colour barrier was to race in sports: a disciplinary strategy to maintain what is considered the "natural" sports categories of a certain era.